Development of a dynamic market penetration model for technology based electric home appliances - Sumitri, Jeanne; Sharif, M. N.; Pakorn Adulbhan; Woo, Wai-Ling; Government of Australia (Bangkok : Asian Institute of Technology, 1975)
In this study a general model is developed to forecast the market penetration of some high price electric home appliances. Products which are considered in this research are : black-and-white TV, color TV and refrigerator. The model is developed on the basis of some economic factors, such as household income· distribution and price of the appliance. The increment of the ownerships is formulated as proportional to both fraction of households who .have not bought the appliance yet and those who have owned it already. For luxury items, such as color TV, the market penetration is found not to be influenced much by the households who have the appliance already. The model is modified in forecasting the sale of black-and-white TV after color TV is introduced to the market of the country under study. The modification is based on predicting the percentage of replacement of old black-and-white TV by new ones. The developed model is applied to black-and-white TV in three developing countries : R.O.C., Singapore, and Republic of Korea, color TV in R.O.C. and Singapore, and refrigerator in R.O.C. A procedure is developed to estimate the TV signal receiving range in Korea based on limited data. Color TV was introduced to the market of Singapore last year, no historical data about the sale is available. A technique is presented to forecast the ownerships of this appliance in this country.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand .
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Marketing research; Household appliances